Implementing Marketing Strategy During The Covid-19 Pandemic - Rohmah, Wafrotur; Nugroho, Talitha Shafa Pahlevi; Syah, M. Fahmi Johan; Jamal, Fauziyah Nur (Proceedings International Conference on Education Innovation and Social Science, 2022)
In recent years, the spread of the covid-19 pandemic in Indonesia has caused a decline in marketing. Especially in the service sector. An appropriate marketing strategy is needed to be able to overcome this situation. This study aims to describe marketing strategies and the obstacles faced in implementing marketing strategies during the Covid-19 Pandemic. The type of research used is qualitative research with a case study research design. Data collection techniques were carried out by means of observation, in-depth interviews, and documentation. The results show that (1) the product strategy is carried out by innovating to create new services or diversification product, namely, virtual events, and digital printing services in the non-event sector. Pricing using the cost plus method, provide special prices for clients with large-scale events. Promotion is done door to door and utilizes social media platforms and outdoor advertisements. More strategic offices and warehouses make it easier for clients to reach. The skill, knowledge, and welfare of employees are prioritized for work professionalism. In providing the service process, it refers to SOPs, fast and creative, as well as providing free consulting services for the pre-event process, physical evidence owned, namely buildings and supporting goods. (2) the obstacles faced by Jinawi Indonesia in implementing marketing strategies during the pandemic are capital constraints and the ineffectiveness of online promotion through social media platforms. implications for event organizer companies can innovate new services under pandemic conditions, namely virtual event services and non-event services.